PERLINDUNGAN TERHANAP ANAK SEKOLAH DASAR KORBAN KEKERASAN SEKSUAL: Kekerasan Seksual Terhadap Anak - Zainol Arief (FKIP Universitas Wiraraja, 2025)
Protection of children from sexual violence is regulated separately, especially at the Elementary School level because at that level they are very vulnerable to intimidation and even harassment from people closest to them, both in the family environment, especially in the environment where they study at Elementary School educational institutions that require more attention, therefore there is a need for legal protection for child victims of sexual violence based on Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. The purpose of this study is to provide protection for child victims of sexual violence, both from social rehabilitation and psychosocial assistance during treatment until recovery, providing restitution or compensation and providing protection and assistance at every level of examination starting from investigation, prosecution, to examination in court, so the direction of this research is towards early childhood, especially children in Elementary School who are easily intimidated by people closest to them, especially in Elementary School educational institutions. The type of method used is qualitative with a normative approach and supported by empiricism. The results of this study are towards child protection which can be done through education about reproductive health, religious values, and moral values, carrying out social rehabilitation and psychosocial assistance during treatment until recovery.